Coverage of the 2008-2009 Economic Crisis in the Media and Relationship of the Coverage to Actual Situation - Tauraitė, Vilija (Taikomoji kalbotyra, 2020)
The primary goal of this paper is to examine the coverage of the 2008-2009 economic crisis in the Lithuanian online media as well as its relationship to the actual economic situation and perception of media consumers. The theoretical basis for this research is made up of the theories of agenda-setting and framing. The coverage of the media is assessed on the basis of the corpus of economic reporting in 2006–2014 in two Lithuanian media sources, the news agency BNS and DELFI news website, by analysing the volume and the tone of the reports. The coverage in the media is then compared to some statistical economic indicators.The main findings of the paper are the following:1. The coverage of the crisis in the media reflected rather accurately the actual situation: the fluctuations of the volume of the reports largely followed the timeline of the main events of the crisis. The correlation between the reporting tone and industrial production index as a gauge of the economic situation was rather high, which supports the adequacy of the coverage. The relationship between the reporting and economic indicators was found to be stronger in the case of the BNS than in DELFI.2. Negative reports were found to be dominating over positive ones. It is partially inevitable due to the context of the crisis, but the effect of the general media negativity bias cannot be ruled out either.3. During the year of the worst economic situation, the number of the reports of both highly negative and highly positive tone increased, but the volume of the two extremes decreased with the improvement of the economic situation. This might suggest that the media was aiming to counterweight the flow of very negative news during the crisis.4. On average, the tone of the BNS news agency coverage was more positive than that of DELFI. The factors behind this trend could be the linguistic features of the reporting style (usage of intensifying modal words as well as negatively or positively image-evoking lexis) and the intention to attract attention from the audience.5. Certain asymmetry was noticed in the public reaction to the coverage of the crisis in the media as media consumers reacted more rapidly and for a longer time period to the deterioration in the reporting tone than to its improvement.6. The correlation to media coverage was stronger in the case of the consumer sentiment indicator rather than in the case of the indicator for consumer behaviour (retail trade turnover index).It should be noted that the analysis was limited to only two media channels, so the inclusion of other media channels, especially television, could make such research more informative. Further research could include an additional corpus of reports with such keywords as “recession”, “recovery”, “growth”, “unemployment” and similar items. An analysis of the effects of linguistic factors alone on the reporting tone could also provide some interesting insights. Research on the coverage tone in relation to different subjects (economy, companies and political events) could be another valuable addition to the study.
Keywords: crisis; media coverage; tone; agenda-setting; framing